Line Graphs of Monogenic Semigroup Graphs - Nihat Akgunes; Yasar Nacaroglu; Sedat Pak (Journal of Mathematics)
The concept of monogenic semigroup graphs ΓSM is firstly introduced by Das et al. (2013) based on zero divisor graphs. In this study, we mainly discuss the some graph properties over the line graph LΓSM of ΓSM. In detail, we prove the existence of graph parameters, namely, radius, diameter, girth, maximum degree, minimum degree, chromatic number, clique number, and domination number over LΓSM.